Chemical composition and bioactive characterisation of Impatiens walleriana - Pires Junior, Eleomar de O. (2018)
The attractive colour characteristics of the flowers of the species Impatiens walleriana have been arousing great interest in the food industry, which is looking for potential natural sources of colouring ingredients. In this sense, the present work focused on the chemical and bioactive characterization of pink and orange flowers of I. walleriana. The phenolic compounds were determined by HPLC-DAD-ESI/MS; in addition, different bioactivities (antioxidant, antimicrobial, anti-inflammatory and cytotoxicity) were also analysed. Both samples studied showed significant amounts of phenolic compounds, especially phenolic acids, flavonoids, and anthocyanins, which justifies the excellent performance in the different bioactivities studied. The orange variety, despite having a greater variety of phenolic compounds, showed a total amount of compounds lower than the pink variety. Overall, the flowers of I. walleriana emerge as a promising resource to be explored by the food industry.